The Eugene Garbáty Collection of European Art. Issue 3 (September 2014) - Reed, Victoria
Little has been written about the art collection of Eugene Garbáty, a Jewish industrialist from Berlin who fled Germany and settled in the United States in the late 1930s. Yet, many American museum collections include works of art that belonged to Garbáty, and the Museum of Fine Arts, Boston (MFA) is no exception; between the 1940s and the 1960s, the MFA acquired thirty-four works of European painting, sculpture, and decorative art from him. Based on a study of the provenance of these objects, this article offers preliminary observations on the formation of Garbáty's collection, its fate during World War II, and its dispersal within the United States.